Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1111/j.1464-410x.2008.07939.x
|View full text |Cite
|
Sign up to set email alerts
|

Solifenacin in the treatment of urgency and other symptoms of overactive bladder: results from a randomized, double‐blind, placebo‐controlled, rising‐dose trial

Abstract: OBJECTIVES To examine the effects of the antimuscarinic agent solifenacin on urinary urgency, using a range of novel and established outcome measures, as urgency is the principal symptom of the overactive bladder syndrome (OAB). PATIENTS AND METHODS The study (SUNRISE, solifenacin in the treatment of urgency symptoms of OAB in a rising dose, randomized, placebo‐controlled, double‐blind, efficacy trial) was a randomized, double‐blind, 16‐week, placebo‐controlled, multicentre study of solifenacin 5/10 mg in 863 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
83
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(100 citation statements)
references
References 15 publications
12
83
0
5
Order By: Relevance
“…The mean number of urgency episodes per 24 h, the primary endpoint, decreased by 3.91 (from 6.15 to 2.24) with solifenacin and by 2.73 (from 6.03 to 3.30) with placebo ( P < 0.0001) (23). Solifenacin was also significantly more effective than placebo in reducing the mean number of episodes of severe urgency from baseline to endpoint (−2.6 vs. −1.8, P < 0.001) (24). Median warning time (defined as the time from first sensation of urgency to voiding), a secondary endpoint, increased 31.5 s (baseline, 67.8 s) with solifenacin, significantly longer ( P = 0.008) than the median increase of 12 s (baseline, 65.0 s) observed with placebo (23).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The mean number of urgency episodes per 24 h, the primary endpoint, decreased by 3.91 (from 6.15 to 2.24) with solifenacin and by 2.73 (from 6.03 to 3.30) with placebo ( P < 0.0001) (23). Solifenacin was also significantly more effective than placebo in reducing the mean number of episodes of severe urgency from baseline to endpoint (−2.6 vs. −1.8, P < 0.001) (24). Median warning time (defined as the time from first sensation of urgency to voiding), a secondary endpoint, increased 31.5 s (baseline, 67.8 s) with solifenacin, significantly longer ( P = 0.008) than the median increase of 12 s (baseline, 65.0 s) observed with placebo (23).…”
Section: Discussionmentioning
confidence: 92%
“…In a double-blind, placebo-controlled trial, the efficacy and tolerability of solifenacin treatment for OAB was assessed (23,24). Patients were randomized to once-daily solifenacin (5/10 mg) or placebo for 12 (23) or 16 (24) weeks.…”
Section: Discussionmentioning
confidence: 99%
“…All of the patients were diagnosed with idiopathic OAB and demonstrated no prior surgery on lower urinary tract, urinary tract infections and neurological abnormalities based on a detailed history of symptoms, physical examinations and urinalysis. Patients documented the 3-day frequency-volume chart, as well as the Patient's Perception of Intensity of Urgency Scale (PPIUS), 8 at every voiding. The PPIUS is a 5-point scoring system that incorporates the frequency-volume chart and describes the degree of urgency and urgency incontinence felt by the patient.…”
Section: Methodsmentioning
confidence: 99%
“…Cardozo et al, 2008;Chapple, 2005) Another recent study confirmed that solifenacin was significantly more effective in reducing the mean number of severe urgency episodes with or without incontinence per 24 hours, improved urgency symptoms and was well tolerated. Additionally, no cognitive impairment has been associated with this drug.…”
Section: Solifenacinmentioning
confidence: 94%